Jaminan Kepastian Hukum Atas Pinjaman Modal Terhadap Kegiatan Usaha Rumah Tangga Berdasarkan Undang-Undang Republik Indonesia Nomor 10 Tahun 1998 Tentang Perubahan Atas Undang-Undang Nomor 7 Tahun 1992 Tentang Perbankan (STUDI DI PT. BANKALTIMTARA CABANG SAMARINDA) - Namira Meidina Aulia; Parlindungan Pasaribu (Yuriska: Jurnal Ilmiah Hukum, 2019)
This study aims to find out the form of Legal Assurance Guarantee on Capital Lending of Household Business Activity in terms of Law Number 10 the year 1998 Concerning Amendment to Law Number 7 of 1992 Concerning Banking and Constraints in Capital Lending Process by Household Business Actor in Banking. This research is normative law research that comes from primary law material and secondary law material. The result of the research shows that the form of Assurance of Legal Certainty to the Capital Lending of Household Business Activity, namely Forms of Guarantee that is in Tangible Assurance Form, Intangible Assurance Form, Form of Guaranteed Movement, Form of Assurance of Permanent / Unmoving Equipment. And the form of legal certainty to the lending of the capital of household business activity that is in the written form contained in the Letter of Credit Agreement (SPPU). Then to the Constraints in Capital Loan Processing by Household Business Actors in Banking namely Incomplete and Valid Data, Procedure of business loan to bank is often time-consuming, the process is complicated and the conditions are not easily fulfilled, Business Considered Less Productive, Absence of Collateral / Additional Guarantees, Bad Business Legality, Bad Credit History. Therefore, it is suggested that in the future, the bank can further facilitate the debtor in applying for the household capital loan, although the bank applies the prudential principle by requiring the collateral to guarantee its legal certainty, the bank is also expected not based on the collateral aspect but also the bank consider other aspects.